Peramalan Penjualan Pupuk Menggunakan Metode Trend Moment - Ulfa, Ulia; Sumijan; Nurcahyo, Gunadi Widi (Jurnal Informatika Ekonomi Bisnis, 2019)
Aneka Tani Mandiri Trade Unit is a fertilizer sales shop in the city of Padang. From year to year sales of fertilizers in UD. Aneka Tani Mandiri experiences fluctuations where it is difficult to predict sales increases and decreases every month. The problem that most often occurs in this store is often experiencing shortages and excess stock of goods, this is very likely to occur because many of its items are not sold out and many items are needed by consumers but insufficient stock of goods. Another result is that the profits from the store should be more reduced, with this problem the store must be able to predict how many items will be sold and how many items must be provided in the following month, by knowing the number of items to be sold, the deficiency or excess stock of goods can be avoided. So for that the research was conducted using the Trend Moment Method to predict and predict fertilizer stock that will be provided for the following month. So that will increase sales turnover of the store. By building a fertilizer sales forecasting system using the Trend Moment method which is assisted by the PHP and MySQL programming languages ​​can produce ZA fertilizer sales predictions with success rates above 75%.